An investigation on tourism consumers' choice behavior towards tour destination loyalty - Hossain, Md Enayet (Curtin University, 2013)
This study investigates the factors that influence tourism consumers’ choice behavior towards tour destination loyalty. Loyalty behavior has generally been accredited as a most desirable area for academics and practitioners because, among other things, it is thought that the marketing promotion costs needed to attract loyal visitors are lower than those required for non-loyal visitors. A loyalty is a positive indicator of tourism consumers’ satisfaction towards the destination and its services which are mainly used for successful business operations. The positive outlook of high repeaters increases their possibility to come back to same destination in future.With theses grounds, this research investigates the theoretical and empirical evidence on the causal relationships among different factors (intrinsic cues, destination brand image, warranty facilities, price, quality, risk, sacrifice, satisfaction, and loyalty) in the formation of destination loyalty. Recently few studies have focused on the moderating effect of gender, age, and level of education in the destination loyalty process. Therefore, the current research has further investigated the effect of moderating variables on relationships of different factors in the destination loyalty process, which has not previously been given much attention. In addition, this research also presents an extensive explanation on reflective and formative constructs to discuss the higher order multidimensional constructs that influence the loyalty process.This research methodologically adopts a mixed method approach. In the first phase, the literature review identified the Information Processing Theory (IPT), Theory of Reasoned Action (TRA), Theory of Planned Behavior (TPB), as relevant to the study of actual behavioral (loyalty) along with an extensive literature review. Then an initial research model was developed to test the loyalty empirically. The second phase consists of a qualitative data collection from 25 experienced visitors using semi-structured questionnaires. The field data is analyzed using a two stage (inductive and deductive) content analysis technique. The initial research model is then refined based on the findings of this phase. Altogether, twelve constructs are identified. In the ensuing quantitative phase, a survey instrument is developed to test a range of hypotheses based on the research model. First, a pilot study is conducted on the responses from 145 visitors. The instrument is then refined and administered in a national survey which resulted in 602 useable responses. A non response bias test has also been conducted to look for whether there are different opinions between respondents and non-respondents in the survey. Partial Least Squares (PLS) based Structural Equation Modeling (SEM) approach is applied to test the 22 relationships in the research model. In addition, a multi-group analysis, and analysis of higher order constructs of PLS are also employed.The result of this research presents in total 15 relationships which are statistically significant. The overall explanatory power of the model is very much satisfactory as explained 64% of the variance on loyalty towards Cox’s Bazar, Bangladesh. It is found that perceived satisfaction is the main antecedent of destination loyalty. It is also found that Perceived quality and perceived sacrifice are important influential factors in determining the perceived satisfaction. Overall the findings confirm that the perceived destination loyalty (PDL) is a function of multidimensional factors including formative and reflective measures. Furthermore, the findings have confirmed that consumers’ choice decision making at the destination level is a sequential process. In addition, although the moderating effects of gender, age, and level of education in the destination loyalty process are not found to be significant, some relationships in the model are very much significant.The theoretical contribution of this research lies in the development of a parsimonious destination loyalty model that has successfully been incorporated using different constructs from the existing literature and based on three prominent behavioral theories; IPT, TRA, and TPB. First of all, this research provides a significant contribution to the existing knowledge presenting the role of intrinsic and extrinsic cues on quality, risk, sacrifice, and satisfaction in the destination loyalty behavior. Secondly, the investigation of the research contributes to current knowledge by filling the gap of moderating effects of tourism consumer demographics in the PDL process especially for third world countries like Bangladesh. Finally, using formative and reflective measures this study has added a new dimension to effective travel and tourism operational strategies. In practice perhaps, a major contribution of this research is the implication for the destination operators to endeavor to enhance a sustained loyalty at the destination level.